HUBUNGAN ANTARA KOMITMEN ORGANISASIONAL DAN GAYA MANAJEMEN KONFLIK KARYAWAN BANK MILIK PEMERINTAH DAERAH TINGKAT II DI PROVINSI DIY - Heru Kristanto (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan, 2015)
The aim of this study is to examine the impact of employee commitment on conflict management style with object, circumstances, and conditions of Indonesia. The respondent of this study is 261 employees of government-owned banks from five regencies in the Province of Daerah Istimewa Yogyakarta. The data were analized by implementing Multiple Linear Regression Technique. The results show that there is an indicationthat employees who have both commitment to the community and to the supervisor tends to implement integrating and avoiding style. Employees who have a commitment to superior, tends to carry out domi nating and obliging approach. Whereas, employees who have a commitment to society, tend to implementing compromising approach. Implication of this study for future research is carry out longitudinal or ex perimental study.